Long Noncoding RNA CASC2 Facilitated Wound Healing through miRNA-155/HIF-1α in Diabetic Foot Ulcers. (24th June 2022) - He, Minjie; Tu, Liang; Shu, Ruo; Meng, Qi; Du, Sicheng; Xu, Zhao; Wang, Shaoyun
Abstract : Diabetic foot ulcers (DFU) are among the serious complications which are closely linked to diabetes mellitus. However, there is still a lack of accurate and effective standard prevention and treatment programs for DFU. In this manuscript, we have investigated the function of lncRNA cancer susceptibility candidate 2 (CASC2)/miR-155/hypoxia-inducible factor 1-alpha (HIF-1 α ) in the wound healing of DFU. We have analyzed lncRNA CASC2`s expression in the marginal tissues of ulcers in patients and mice with DFU. Additionally, the interaction relationship and mechanism between lncRNA CASC2, miR-155, and HIF-1 α were determined, which proved the effects of lncRNA CASC2/miR-155/HIF-1 α on fibroblasts apoptosis, proliferation, and migration. According to our study, the lncRNA CASC2's expression was low in the tissues of ulcers of DFU mice and patients. lncRNA CASC2's overexpression promoted fibroblasts migration, proliferation, and inhibited apoptosis and was beneficial for the healing of wounds, preferably in the DFU mice. In addition, lncRNA CASC2 directly targets miR-155 and HIF-1 α functions as miR-155's target gene. Overexpression of miR-155 abrogated the function of lncRNA CASC2. Similarly, HIF-1 α 's inhibition has reversed the effect of miR-155 downregulation on fibroblasts. In general, overexpression of lncRNA CASC2 facilitated wound healing through miR-155/HIF-1 α in DFU.